PELINDUNGAN HAK CIPTA KARYA SINEMATOGRAFI ATAS PENGGUNAAN AI GENERATI DI BERBAGAI PLATFORM MEDIA SOSIAL - Rizka Aminni Putri; Saidin Saidin; Jelly Leviza (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstrack: The current development of information and communication technology has led humans to use the assistance of Generative AI (artificial intelligence) technology to produce various new works, including cinematographic works circulating on social media. However, the emergence of Generative AI has raised new legal issues, because in its use many works have the potential to violate copyright, especially when this technology is used to modify cinematographic works owned by other parties on social media platforms. This study aims to analyze legal certainty, the form of legal liability for the use of Generative AI, and review the form of legal protection for cinematographic works modified using Generative AI on social media without permission. This research is a normative juridical legal research with a descriptive analytical nature. The data used are secondary data consisting of primary, secondary, and tertiary legal materials. Data collection techniques and data were carried out through literature studies. Data analysis used normative analysis methods. The results of the study indicate that legal certainty in the use of Generative AI is currently still not achieved because the Copyright Law is still oriented towards humans as creators. The forms of legal liability that can be applied include civil, criminal, and administrative aspects, while legal protection is provided preventively through takedown mechanisms and repressively through compensation lawsuits and criminal sanctions. The conclusion of this study is that the protection of copyright in cinematographic works for the use of Generative AI on social media platforms creates legal uncertainty that needs to be addressed immediately through regulatory updates and strengthening copyright enforcement policies in the digital era. The formation of specific regulations regarding liability for works involving Generative AI technology is an important step towards realizing legal certainty, justice, and benefits for all parties involved. Keyword: Copyright, Cinematographic Works, Generative AI, Social Media, Legal Protection. Abstrak: Perkembangan teknologi informasi dan komunikasi saat ini membuat manusia menggunakan bantuan teknologi  AI Generatif (kecerdasan buatan) dalam menghasilkan berbagai karya baru, termasuk karya sinematografi yang beredar di media sosial. Namun, kemunculan AI Generatif telah menimbulkan persoalan hukum baru, karena dalam penggunaannya banyak karya yang berpotensi melanggar hak cipta terutama ketika teknologi ini digunakan untuk memodifikasi karya sinematografi milik pihak lain di platform media sosial. Penelitian ini bertujuan untuk menganalisis kepastian hukum, bentuk tanjung jawab hukum atas penggunaan AI Generatif serta meninjau bentuk perlindungan hukum terhadap karya sinematografi yang dimodifikasi menggunakan AI Generatif di media sosial tanpa izin. Penelitian ini adalah penelitian hukum yuridis normatif dengan sifat penelitian dekskriptif analitis. Data yang digunakan adalah data sekunder yang terdiri dari bahan hukum primer, sekunder dan tersier. Teknik dan pengumpulan data dilakukan dengan studi kepustakaan. Analisis data menggunakan metode analisis normatif. Hasil penelitian menunjukkan bahwa kepastian hukum dalam penggunaan AI Generatif saat ini masih belum tercapai karena dalam UUHC masih berorientasi pada manusia sebagai pencipta. Bentuk tanggung jawab hukum yang dapat diterapkan meliputi aspek perdata, pidana serta administratif, sementara perlindungan hukum diberikan secara preventif melalui mekanisme takedown dan represif melalui gugatan ganti rugi maupun sanksi pidana. Kesimpulan dari penelitian ini adalah pelindungan hak cipta karya sinematografi atas penggunaan AI Generatif di platform media sosial menimpulkan ketidakpastian hukum yang perlu segera diatasi melalu pembaruan regulasi dan penguatan kebijakan penegakan hak cipta di era digital. Pembentukan aturan khusus mengenai tanggung jawab atas karya yang melibatkan teknologi AI Generatif menjadi langkah penting untuk mewujudkan kepastian, keadilan dan kemanfaatan hukum bagi seluruh pihak terkait. Kata kunci: Hak Cipta, Karya Sinematografi, AI Generatif, Media Sosial, Pelindungan Hukum.